Cidade, processos de criação e intervenções: práticas poe[lí]ticas na dimensão ordinária da experiência estética - AZEVEDO, Fernando de Pádua Mesquita de (Universidade Federal do Pará, 2017)
In this dissertation, I propose we try experiential possible displacements of research traversed by vivencias and other events in ordinary dimension of aesthetic experience. The matters discussed herein address issues concerning the practices of creative doing experienced in everyday city. Propositions of a rhizomatic approach in víeis deleuze-guattariano on aspects relating to artistic processes that occur in parallel to the mechanisms of collective agency. Aproprio me the meaning of scripture disseminated by Jacques Derrida, as a strategy to traffic over the plots that involve everyday situations in temporality proper to do.